LOGARITMOS: CONCEITOS, APLICAÇÕES E ABORDAGEM DO TEMA NOS VESTIBULARES DA UEPG - Marra, Marina (2014)
The logarithms have numerous applications in mathematics and in other areas of knowledge. In some, of them, the logaritms are considered essential and in others they are facilitators of calculations. In this work we present a brief historical research of logarithms, through the leading mathematicians involved and their contributions. Additionally, we define logarithms and we indicate their properties. In spotlight, we present possibilities for integration of logarithms with other mathematical content and with various other areas of knowledge. Finally we present how the UEPG (Universidade Estadual de Ponta Grossa) has addressed the issue in his last college entrance exams.